Kiwari: Inquiry Smart Module (Investigation Fiction Case-Based) as an Approach to Integrative Science for Student's Analytical Thinking Competencies in Senior High School - Arisna, Definda Putri; Sakina Rizqiani; Ramadhan, Muhamad Fahreza (SEAQIS Journal of Science Education, 2023)
The ability to think analytically and critically is one of the keys to carrying out education, which can make students understand comprehensive information and associate between components. However, to train the students’ analytical and critical thinking skills, their interest and excitement towards the learning process must be approached. This research was conducted to attract and increase students' interest in learning Biology and Chemistry (Integrative Science), providing an alternative or inspiration for inquiry science learning media to train students’ analytical thinking skills and creating a Learner-Centred class. The method used in this study is Research and Development (4D Model); the module design includes the Define, Design, and Development stages. Furthermore, the Two Group Randomised Experiment Method was used to test and measure the feasibility of the Kiwari Module. In this research, the parameters used to test the effectiveness of the module include the parameters to measure in terms of students' interest or excitement in learning, the use in terms of honing students' analytical thinking skills, and the use in studying Biology and Chemistry material, as well as student participation or contribution actively on learning. This study found that the module was said to be effective in increasing students' interest in learning Biology and Chemistry by up to 92%. The analytical uses of the module were scored 4.5 out of 5 by the material experts and suitable for use as a science inquiry learning media option up to 71%. The module was 70.6%, involving students participating actively in the class (Learner-Centred Class).